Exact flow equations and the U(1) problem - Pawlowski, Jan M. (Physical review. D, Particles, fields, gravitation, and cosmology, 1998)
The effective action of an SU(N)-gauge theory coupled to fermions is evaluated at a large infrared cutoff scale k within the path integral approach. The gauge field measure includes topologically non-trivial configurations (instantons). Because of the explicit infrared regularization, there are no gauge field zero modes. The Dirac operator of instanton configurations shows a zero mode even after the infrared regularization, which leads to UA(1)-violating terms in the effective action. These terms are calculated in the limit of large scales